A proposed fuel cell vehicle for reducing CO2 emissions and its contribution to reducing greenhouse gas emissions - Mourad, Mohamed (International Journal of Engineering and Technology, 2014)
Because of their high efficiency and low emissions, fuel cell vehicles are undergoing extensive research and development. When considering the introduction of advanced vehicles, a complete evaluation must be performed to determine the potential impact of a technology on carbon dioxide (CO2) and greenhouse gases emissions. However, the reduction of CO2 emission from the vehicle became the most important objective for all researches institutes of vehicle technologies worldwide. There interest recently to find unconventional methods to reduce greenhouse gas emission from vehicle to keep the environment clean. This paper offers an overview and simulation study to fuel cell vehicles, with the aim of introducing their main advantages and evaluates their influence on emissions of carbon dioxide from fuel cell vehicle and compares advanced propulsion technologies on a well-to-wheel energy basis by using current technology for conventional and fuel cell. The results indicate that the use of fuel cells, and especially fuel cells that consume hydrogen, provide a good attempt for enhancing environment quality and reducing greenhouse gas (GHG) emissions. Moreover, the emission reduction percentage of fuel cell vehicle reaches to 64% comparing to the conventional vehicle. Keywords: Fuel Cell Electric Vehicle, Performance, Simulation, Driving Cycle, CO2 Emissions, Greenhouse Gas Emissions, Fuel Consumption.